Designing a potent multivalent epitope vaccine candidate against Orientia tsutsugamushi via reverse vaccinology technique - bioinformatics and immunoinformatic approach - Panda, Subhasmita; Swain, Subrat Kumar; Sahu, Basanta Pravas; Mahapatra, Soumya Ranjan; Dey, Jyotirmayee; Sarangi, Rachita; Ranade, Anu Vinod; Mishra, Namrata (Frontiers in Immunology, 2025)
Scrub typhus is a life-threatening, undifferentiated febrile illness caused by a gram-negative bacterium, Orientia tsutsugamushi. The bacterial strain is a global health concern that should be considered. Despite several years of effort for the development of an effective immunogenic vaccine, no successful licensed vaccine is available. The aim of the study is to construct an epitope response using a reverse vaccinology approach. The TSA56 and ScaA proteins combined can be the most promising subunit vaccine candidates against O. tsutsugamushi. B-cell, CTL, and HTL epitopes were predicted, and subsequently, all the epitopes were linked by KK, AAY, and GPGPG linkers, respectively, along with an adjuvant at the N-terminal region. Furthermore, molecular docking and MD simulations were performed that exhibited a higher affinity towards TLR-2. A total of 16 linear B-cells, 6 CTL, and 2 HTL epitopes were identified and validated. The final vaccine construct showed high antigenicity, stability, and solubility. Molecular docking and MD simulations indicated strong binding interactions with TLR-2 and a stable vaccine-receptor complex. The expression of the vaccine in pET28a (+) vector was successfully implemented via in silico cloning as well as significant results from immune simulation demonstrated the efficacy of the vaccine in the immune cell interaction during the innate and adaptive immune responses immune simulation. In conclusion, the outcome suggested that the newly developed vaccine will be a promising candidate for controlling and providing definitive preventive measures against scrub typhus if further investigation is conducted experimentally.